Rupture du ligament croisé antérieur chez le sportif: répercussion sur la densité minérale osseuse du genou - Boudenot, A.; Pallu, S.; Lespessailles, E. (Science & Sports, 2013)
Severe knee injuries occurring in sports are known to lead to early osteoarthritis. The aim of this study was to characterize the epiphyseal bone mineral density (BMD) on the knee in order to analyze the potential impact of anterior cruciate ligament (ACL) rupture on epiphyseal bone. Eight competitive athletes (men and women) were recruited with unilateral ACL rupture and a median time since surgery of 19.8 months (9.2-75.7). Dual Energy X-ray Absorptiometry (DXA) was used to determine the body composition and the BMD at the whole body and at the knee epiphysis. Proximal tibia and distal femur BMD epiphysis were significantly lower in the injured leg compared to uninjured leg, respectively 1.230 ± 0.292 vs. 1.307 ± 0.339 g/cm2, at the tibia and 1.487 ± 0.393 vs. 1.587 ± 0.371 g/cm2 at the femur. Moreover, injured and uninjured whole legs BMD were not statistically different (injured 1.377 ± 0.200 vs. uninjured 1.413 ± 0.190 g/cm2, P = 0.12). Our results indicate a relationship between epiphyseal bone and knee injury. Changes observed could be early physiopathological changes involved in post-traumatic osteoarthritis at the knee.